Баба Яга: [русская народная сказка ; для чтения взрослыми детям / в обработке А. Н. Афанасьева] (Проф-Пресс, 2019)
Экземпляры: ф-12 (20200916) / Инвентарный номер: 55891 / Цена: 35.00 / Сис.шифр: Д / Авт.знак: Б 12 / ГРНТИ: 17.82.93 / ББК: 82.3(0)